Matrix changes in articular cartilage in the knee of patients with rheumatoid arthritis after biological therapy: 1-year follow-up evaluation by T2 and T1ρ MRI quantification. Issue 11 (November 2018) - Hirose, J.; Nishioka, H.; Tsukano, M.; Matsubara, S.; Usuku, K.; Mizuta, H.
Abstract : Aim: To estimate the morphological changes in the articular cartilage of the knees of patients with rheumatoid arthritis treated with biological disease-modifying anti-rheumatic drugs (bDMARDs). Materials and methods: Cartilage-specific magnetic resonance imaging (MRI) results, including T2 and T1ρ mapping of the femorotibial joint of 17 patients, were obtained before and 1 year after starting treatment with bDMARDs. Regions of interest were selected on the sagittal images of the cartilage of the medial and lateral femoral condyles (MFC, LFC) and the tibial plateau (MTP, LTP). Cartilage thickness, T2, and T1ρ were measured, and the correlations of their changes were evaluated. Results: The mean changes in cartilage thickness tended to decrease in all four condyles, and the rate was significant in the MFC. T2 and T1ρ tended to increase, and T2 in the MFC significantly increased. Changes in cartilage thickness after 1 year showed a moderate correlation with the baseline T2 in the MFC as well as changes in T2 in the MTP. Conclusions: Decreasing cartilage thickness and matrix changes appeared in the MFC after 1 year of treatment with bDMARDs. Microstructural damage of the cartilage at baseline is a predictor for further cartilage damage in the knee joint, even if treatment with bDMARDs is effective. Highlights: The T2 values in the MFC increased after 1 year of biological treatment. The cartilage thickness decreased in the MFC during the treatment. These changes in cartilage thickness correlated with the baseline T2. Microstructural cartilage damage affects further cartilage damage.